Essential oncology nursing care along the cancer continuum - Young, Annie M.; Charalambous, Andreas; Owen, Ray I.; Njodzeka, Bernard; Oldenmenger, Wendy H.; Alqudimat, Mohammad R.; So, Winnie K W (My University, 2020)
Oncology nurses are at the heart of tackling the increasing global burden of cancer. Their contribution is unique because of the scale and the diversity of care roles and responsibilities in cancer care. In this Series paper, to celebrate the International Year of the Nurse and Midwife, we highlight the contribution and impact of oncology nurses along the cancer care continuum. Delivering people-centred integrated care and optimal communication are essential components of oncology nursing care, which are often played down. More oncology nurses using, doing, and leading research will further show the key nursing impact on care as part of a team. The oncology nurse influence in saving lives through prevention and early detection of cancer is noteworthy. Supportive care, the central pillar of oncology nursing, enables and empowers people to self-manage where possible. Globally, oncology nurses make a great positive difference to cancer care worldwide; their crucial contribution throughout the continuum of care warrants the inclusion and promotion of nursing in every country's cancer strategy. 2020 is the year of the nurse: let us take this learning to the future.
Keywords: Continuity of Patient Care; Delivery of Health Care; Integrated; Neoplasms; Nurse's Role; Nurse-Patient Relations; Oncology Nursing; Patient Care Team; Patient-Centered Care; Practice Patterns; Nurses'